Architecting cloud native serverless solutions : design, build, and operate serverless solutions on cloud and open-source platforms - CM, Safeer (Packt Publishing, 2023)
Get up and running with serverless workloads across AWS, Azure, GCP, Kubernetes, and virtual machines with real-life examples and best practices for design, development, and security of serverless applications Purchase of the print or Kindle book includes a free PDF eBook Key Features Learn with DIY projects and step-by-step instructions for different serverless technologies and vendors Explore detailed sections on running serverless workloads across Kubernetes and virtual machines Discover Cloudflare Serverless Solutions to modernize your web applications Book Description Serverless computing has emerged as a mainstream paradigm in both cloud and on-premises computing, with AWS Lambda playing a pivotal role in shaping the Function-as-a-Service (FaaS) landscape. However, with the explosion of serverless technologies and vendors, it has become increasingly challenging to comprehend the foundational services and their offerings. Architecting Cloud Native Serverless Solutions lays a strong foundation for understanding the serverless landscape and technologies in a vendor-agnostic manner. You'll learn how to select the appropriate cloud vendors and technologies based on your specific needs. In addition, you'll dive deep into the serverless services across AWS, GCP, Azure, and Cloudflare followed by open source serverless tools such as Knative, OpenFaaS, and OpenWhisk, along with examples. You'll explore serverless solutions on Kubernetes that can be deployed on both cloud-hosted clusters and on-premises environments, with real-world use cases. Furthermore, you'll explore development frameworks, DevOps approaches, best practices, security considerations, and design principles associated with serverless computing. By the end of this serverless book, you'll be well equipped to solve your business problems by using the appropriate serverless vendors and technologies to build efficient and cost-effective serverless systems independently. What you will learn Understand the serverless landscape and its potential Build serverless solutions across AWS, Azure, and GCP Develop and run serverless applications on Kubernetes Implement open source FaaS with Knative, OpenFaaS, and OpenWhisk Modernize web architecture with Cloudflare Serverless Discover popular serverless frameworks and DevOps for serverless Explore software design and serverless architecture patterns Acquire an understanding of serverless development and security best practices Who this book is for This book is for DevOps, platform, cloud, site reliability engineers, or application developers looking to build serverless solutions. It's a valuable reference for solution architects trying to modernize a legacy application or working on a greenfield project. It's also helpful for anyone trying to solve business or operational problems without wanting to manage complicated technology infrastructure using serverless technologies. A basic understanding of cloud computing and some familiarity with at least one cloud vendor, Python programming language, and working with CLI will be helpful when reading this book.